Regression for Economics - Naghshpour, Shahdad (Business Expert Press, 2012)
Ebook from IG Library ; Regression analysis is the most commonly used statistical method in the world. It is used in economics and many other fields. This book is suitable for all business students and executives who need to understand the concept of regression for practical and professional purposes.